2004
DOI: 10.1086/378920
|View full text |Cite
|
Sign up to set email alerts
|

Predation Intensity Does Not Cause Microevolutionary Change in Maximum Speed or Aerobic Capacity in Trinidadian Guppies (Poecilia reticulataPeters)

Abstract: We measured maximal oxygen consumption (VO(2max)) and burst speed in populations of Trinidadian guppies (Poecilia reticulata) from contrasting high- and low-predation habitats but reared in "common garden" conditions. We tested two hypothesis: first, that predation, which causes rapid life-history evolution in guppies, also impacts locomotor physiology, and second, that trade-offs would occur between burst and aerobic performance. VO(2max) was higher than predicted from allometry, and resting VO(2) was lower t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 52 publications
4
33
1
Order By: Relevance
“…critical swimming performance) as a cost of improved unsteady swimming performance, which has been demonstrated in several fish species (Reidy et al, 2000;Langerhans, 2009;Oufiero et al, 2011). However, in other studies, predation was found to generate no effect on either unsteady or steady swimming performance (or on both types of swimming performance) (Chappell and Odell, 2004;Fu et al, 2012). These findings suggest that the effect of predation stress on swimming performance might be species specific.…”
Section: Introductionmentioning
confidence: 82%
“…critical swimming performance) as a cost of improved unsteady swimming performance, which has been demonstrated in several fish species (Reidy et al, 2000;Langerhans, 2009;Oufiero et al, 2011). However, in other studies, predation was found to generate no effect on either unsteady or steady swimming performance (or on both types of swimming performance) (Chappell and Odell, 2004;Fu et al, 2012). These findings suggest that the effect of predation stress on swimming performance might be species specific.…”
Section: Introductionmentioning
confidence: 82%
“…Maximum burst swimming speed throughout individuals' entire escape response was measured using methods similar to those described previously (Chappell and Odell, 2004). A total of 191 trials were performed in which guppies were placed individually into a circular aquarium (30cm diameter) filled with approximately 4-5cm of water and maintained at the fish's test temperature.…”
Section: Burst Speedmentioning
confidence: 99%
“…Unfortunately, there is only limited evidence for the repeatability of fast-start performances in fish (e.g., Gibson and Johnston 1995;Fuiman and Cowan 2003;Oufiero and Garland 2009;Marras et al 2011), and we are unaware of any studies tracking the relative fortunes of individual fish of known acceleration performance in the field. Several studies have gauged the success of animals of known acceleration performance subjected to predator-prey encounters but only under laboratory conditions (e.g., O'Steen et al 2002O'Steen et al , 2010Chappell and Odell 2004;Walker et al 2005). Our study extends this type of study to the seminatural mesocosm level.…”
Section: Introductionmentioning
confidence: 80%
“…This is similar to the lack of relationship between U crit and maximal sprint swimming velocity in the SPC that we reported previously (Claireaux et al 2007). Other studies using high-speed filming have also reported the relative independence of acceleration performance and endurance or aerobic performance in fish (e.g., Chappell and Odell 2004;Oufiero and Garland 2009). …”
Section: Group Differences In Acceleration Performance Measured With mentioning
confidence: 93%